Investigating the Inclusive-Performance Tradeoff in Agricultural Cooperatives: Evidence from Nepal. (November 2022) - Miller, Scott; Mullally, Conner
Highlights: We conduct a descriptive analysis of the tradeoffs between inclusiveness and performance in agricultural cooperatives. We separately analyze extensive (broad membership) and intensive (participation in cooperatives activities) inclusion. Our results suggest that extensive inclusion is negative associated with performance while the opposite is true for intensive inclusion. Abstract: Is there a tradeoff between inclusive membership and market performance in agricultural cooperatives? Prior studies argue that inclusive membership practices damage cooperative performance by increasing internal transaction and coordination costs. Determining the extent of this tradeoff is essential to understanding the role that cooperatives play in alleviating poverty. Previous studies have largely overlooked the extent to which organizational activities are inclusive of existing members. We expand the definition of inclusive membership to account for extensive as well as intensive inclusion, where the former describes the diversity of a cooperative's membership and the latter refers to including existing members in group activities. We examine the inclusive-performance tradeoff with respect to both dimensions of inclusion. Our results suggest that extensive inclusion is associated with lower market performance, while intensive inclusion is associated with higher market performance. This indicates that both extensive and intensive inclusion have a meaningful, but opposite, association with a cooperative's ability to achieve market performance.